2021
DOI: 10.1016/j.rmcr.2021.101374
|View full text |Cite
|
Sign up to set email alerts
|

Asymptomatic necrotizing myositis in a young male with progressive interstitial lung disease

Abstract: Necrotizing autoimmune myopathy (NAM) is a rare inflammatory process characterized by bilateral proximal muscle weakness and elevated creatinine kinase levels. It is one of the idiopathic inflammatory myopathies. It can be associated with anti-signal recognition particle (SRP) antibody which is commonly seen in middle-aged females. Classic findings on muscle biopsy include muscle fiber necrosis without inflammation. Pulmonary manifestations associated with anti-SRP NAM is rare, and often a challenging correlat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Meanwhile, in a cohort of 460 patients, researchers observed that patients with anti-SRP antibodies developed lung diseases more frequently than those with anti-HMGCR antibodies (Watanabe et al, 2016). Case reports by Below and Bashir (2021) and Baah et al (2021) also indicated that the early onset of pulmonary hypertension in patients might be associated with SRP proteins. Nevertheless, most of these studies focused on inflammatory myopathies, and the relationships between SRP-DGs and other diseases remain to be explored.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, in a cohort of 460 patients, researchers observed that patients with anti-SRP antibodies developed lung diseases more frequently than those with anti-HMGCR antibodies (Watanabe et al, 2016). Case reports by Below and Bashir (2021) and Baah et al (2021) also indicated that the early onset of pulmonary hypertension in patients might be associated with SRP proteins. Nevertheless, most of these studies focused on inflammatory myopathies, and the relationships between SRP-DGs and other diseases remain to be explored.…”
Section: Discussionmentioning
confidence: 99%
“…Radiographic imaging was initially consistent with an NSIP pattern with diffuse ground glass opacities but rapidly progressed to a UIP pattern with fibrotic and inflammatory changes within a mere 18 months. Ultimately, the patient underwent lung transplantation and histology from the explanted lung revealed mixed features of UIP and fibrotic NSIP ( 91 ).…”
Section: Immune Mediated Necrotizing Myopathymentioning
confidence: 99%